Satiric modernism - Rulo, Kevin (Clemson University Press, 2021)
"Satiric Modernism reimagines the history and aesthetics of modernism through the lens of satire through provocative new readings of familiar texts and the introduction of largely unknown works. Kevin Rulo remaps the last hundred years as an era marked distinctively by a new kind of satiric critique of modernity"-- Provided by publisher.
Place of publication taken from publisher's website.
Keywords: Modernism (Literature); American literature -- 20th century -- History and criticism.; English literature -- 20th century -- History and criticism.; Satire -- History and criticism.; Modernisme (Littérature); Littérature américaine -- 20e siècle -- Histoire et critique.; Littérature anglaise -- 20e siècle -- Histoire et critique.; Literary studies: from c 1900.; American literature; English literature; Satire; 1900-1999; Criticism, interpretation, etc.